THE EFFECTIVENESS OF USING VIDEO OF EXPRESSION AS THE MEDIA IN IMPROVING SPEAKING ABILITY IN MAKING GIVING INSTRUCTION EXPRESSION FOR 7A CLASS OF THERESIANA 1 JUNIOR HIGH SCHOOL - Adventina, Anisarini; Sophia B, Th. Cicik; Akbar, Ubaidillah (ETERNAL, 2011)
The objective of this research is to know the effectiveness in using video to teach speaking.Among the problems came from the students themselves usually related to their age andintellectual development and also the differences in individual capability. A total of 35 studentsof 7A observed and tested by the teacher in their activeness and also their ability in producingthe expression after getting the video treatment. The result showed that the ability in speakinggiving instruction expression of the students improved after showing native video in producinginstruction expression.Keywords : video expression, media, speaking ability, giving instruction expression